(3GdQHY GdebfWQ aj GdejbGJs - (3Ydj Hf aVd Gddg Hf eMeO GdeQYTj GdTGaYjs
(3ChdgG (B:s
(3jG ef bOQ GddjGdi hGdCjGe CeG HYO , ajbhd deG aQZJ ef QSGdI GdeLjH , CdaJ QSGdI ai GdebfWQ eTJedI Ydi ebOeI hNGJeI hNeSI YTQ ef GdCHhGH GdebOeI ai JSejI QSheg , efgG GdeQcR , hgh GdHNT s
(3BNQgG (B:s
(3Ke fVQH eG cGf hfbSe GdNGQL Ydi YOO GdXd , hJfbU ef NGQL bOQ eG jchf HUQc hGdCQV , aeG Hbi agh Yebg, hGddg CYde HGdUhGH Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg HYV edGeM GdNW GdaGQSis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B166 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B765s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs